Biofuel Cells for Biomedical Applications: Colonizing the Animal Kingdom. Issue 10 (4th March 2013) - Falk, Magnus; Narváez Villarrubia, Claudia W.; Babanova, Sofia; Atanassov, Plamen; Shleev, Sergey
Abstract Interdisciplinary research has combined the efforts of many scientists and engineers to gain an understanding of biotic and abiotic electrochemical processes, materials properties, biomedical, and engineering approaches for the development of alternative power‐generating and/or energy‐harvesting devices, aiming to solve health‐related issues and to improve the quality of human life. This review intends to recapitulate the principles of biofuel cell development and the progress over the years, thanks to the contribution of cross‐disciplinary researchers that have combined knowledge and innovative ideas to the field. The emergence of biofuel cells, as a response to the demand of electrical power devices that can operate under physiological conditions, are reviewed. Implantable biofuel cells operating inside living organisms have been envisioned for over fifty years, but few reports of implanted devices have existed up until very recently. The very first report of an implanted biofuel cell (implanted in a grape) was published only in 2003 by Adam Heller and his coworkers. This work was a result of earlier scientific efforts of this group to "wire" enzymes to the electrode surface. The last couple of years have, however, seen a multitude of biofuel cells being implanted and operating in different living organisms, including mammals. Herein, the evolution of the biofuel concept, the understanding and employment of catalyst and biocatalyst processes to mimic biological processes, are explored. These potentially green technology biodevices are designed to be applied for biomedical applications to power nano‐ and microelectronic devices, drug delivery systems, biosensors, and many more.